First‐Trimester 3‐Dimensional Power Doppler Placental Vascularization Indices From the Whole Placenta Versus the Placental Bed to Predict Preeclampsia: Does Pregnancy‐Associated Plasma Protein A or Uterine Artery Doppler Sonography Help?. (1st June 2015) - Hannaford, Karen E.; Tuuli, Methodius; Goetzinger, Katherine R.; Odibo, Linda; Cahill, Alison G.; Macones, George; Odibo, Anthony O.
Abstract : Objectives: The purpose of this study was to compare the use of vascular indices derived from the whole placenta to those from the placental bed only for predicting preeclampsia and to determine whether the addition of pregnancy‐associated plasma protein A (PAPP‐A) and mean uterine artery Doppler values improves prediction. Methods: We conducted a secondary analysis of a prospective cohort of women with singletons between 11 and 14 weeks' gestation undergoing sonography for aneuploidy screening. Placental vascularization indices from the whole placenta versus the placental bed were combined with first‐trimester maternal serum PAPP‐A levels, mean uterine artery Doppler values, or the combination of both to predict the development of preeclampsia or early preeclampsia (delivery <34 weeks). The predictive ability of each vascular index was calculated by using areas under receiver operating characteristic curves. The sensitivity of the model for predicting preeclampsia and early preeclampsia at fixed false‐positive rates of 10% and 20% was calculated. Results: Of 570 women, 48 (8.4%) had preeclampsia, and 10 (1.7%) had early preeclampsia. The area under the curve and sensitivity values for the prediction of preeclampsia or early preeclampsia were not different when evaluating the whole placenta versus the placental bed. Additionally, there was no significant improvement when adding PAPP‐A, uterine artery Doppler values, or both. The variables in the model were more sensitive for the prediction of early preeclampsia than preeclampsia. Conclusions: Although placental bed vascular indices are modestly predictive of preeclampsia, the addition of PAPP‐A and uterine artery Doppler values to vascularization indices in the whole placenta or the placental bed did not significantly improve their predictive ability.